The Correlation between Calcium Serum and Calcium Urine Level with the Blood Pressure in Preeclampsia - Deni W. Suryono (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To analyze the differences of calcium serum and calcium urine level in preeclampsia and normal pregnancy, and to analyze the correlation between calcium serum and calcium urine level with blood pressure. Method: This study is a cross sectional study with 44 women with preeclampsia and 45 women with normal pregnancies, that meet our inclusion criteria. The samples were obtained from Dr. Hasan Sadikin Hospital and six satellite hospitals from June to September 2011. The comparison of mean calcium serum and calcium urine level of the preeclampsia group was calculated using Mann-Whitney test, and the correlation between calcium serum and calcium urine level and preeclampsia were calculated using Rank Spearman correlation test. Result: The result of the characteristic test in two groups of study shows that both groups are homogenic and comparable. The mean of calcium serum level in women with preeclampsia (7.97 mg/dl) is lower than in normal pregnancy (8.82 mg/dl) with p